Adult Learners in Transition: New Careers Through Merit-Based Education (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This paper is based on research investigating adult learners who have chosen to pursue a merit-based Bachelor Education.  A merit-based education is a type of educational program designed for individuals who already have gained relevant skills and knowledge through work experience or previous studies. This allows them to receive credit for and validation of their prior learning (VPL)ii and thereby potentially shorten the duration of their new educational program. In this context, we are focusing on adult learners who are at least 30 years old with a higher education degree or a vocational education together with relevant working experiences.  We take a participant perspective, which means that we are interested in these adult learners and their experiences with a new educational culture and profession. Who are they? What motivates them to make a change of career into teaching practice and a pedagogical profession? How does it feel to pursue new career paths? Do academic institutions provide supporting systems to vitalize the adult learners to create meaningful connections between former learning experiences and the new life as a mature student? Adult learners are not only changing careers but are also in a transition of rethinking their professional identity. How do merit-based educations address these questions and how can their prior learning be recognized?